A place-based socioeconomic status index: Measuring social vulnerability to flood hazards in the context of environmental justice. (February 2020) - Chakraborty, Liton; Rus, Horatiu; Henstra, Daniel; Thistlethwaite, Jason; Scott, Daniel
Abstract: This paper proposes a national-level socioeconomic status (SES) index to measure place-based relative social vulnerability and socioeconomic inequalities across Canada. The aim is to investigate how disparities in overall socioeconomic status influence environmental justice outcomes for Canadian flood risk management planning and funding structures. A micro-dataset of the 2016 Canadian census of population was used to derive a comprehensive SES index over 5739 census tracts. The index comprises 49 theoretically-important and environmental policy-relevant indicators of vulnerability that represent diverse aspects of socioeconomic, demographic, and ethnicity status of Canadians. Bartlett's test of sphericity, Kaiser-Meyer-Olkin measure of sampling adequacy, Cronbach's alpha scale reliability, and goodness-of-fit for factor's solution were employed to assess validity, reliability, and consistency in the dataset before applying principal components analysis. Our data revealed 11 statistically-significant multidimensional factors, which together explained 80.86% of the total variation. Levene's homogeneity of variance test disclosed a considerable socioeconomic disparity across census tracts, census metropolitan areas (CMAs), and provinces/territories in Canada. Social vulnerability tends to be geographically stratified across Canada. For example, Drummondville, Saguenay, and Granby CMAs (all in Quebec) had the lowest SES scores, whereas Vancouver and Toronto CMAs had the highest SES scores. Prevalence of spatial variations in the SES scores has significant implications for appraising overall social well-being and understanding the relative social vulnerability of population subgroups. The new place-based SES index has potential for assessing environmental justice outcomes in flood risk management at the census tract level.